Transition Services for Paediatric Inflammatory Bowel Disease: A Multicentre Study of Practice in the United Kingdom. Issue 2 (August 2021) - Ashton, James J.; Narula, Priya; Kiparissi, Fevronia; Spray, Christine; Wilson, David C.; Tayler, Rachel; Howarth, Lucy; Torrente, Franco; Deb, Protima; Cameron, Fiona L.; Muhammed, Rafeeq; Paul, Thankam; et al.
ABSTRACT: Objectives: Patients with paediatric inflammatory bowel disease (IBD) constitute one of the largest cohorts requiring transition from paediatric to adult services. Standardised transition care improves short and long-term patient outcomes. This study aimed to detail the current state of transition services for IBD in the United Kingdom (UK). Methods: We performed a nationwide study to ascertain current practice, facilities and resources for children and young people with IBD. Specialist paediatric IBD centres were invited to contribute data on: timing of transition/transfer of care; transition resources available including clinics, staff and patient information; planning for future improvement. Results: Twenty of 21 (95%) of invited centres responded. Over 90% of centres began the transition process below 16 years of age and all had completed transfer to adult care at 18 years of age. The proportion of patients in the transition process at individual centres varied from 10% to 50%. Joint clinics were held in every centre, with a mean of 12.9 clinics per year. Adult and paediatric gastroenterologists attended at all sites. Availability of additional team members was patchy across the UK, with dietetic, psychological and surgical attendance available in <50% centres. A structured transition tool was used in 75% of centres. Sexual health, contraception and pregnancy were discussed by <60% of teams. Conclusions: This study provides real-world clinical data on UK-wide transition services. These data can be used to develop a national strategy to complement current transition guidelines, focused on standardising services whilst allowing for local implementation. Abstract : Supplemental Digital Content is available in the text